2015
DOI: 10.1063/1.4913202
|View full text |Cite
|
Sign up to set email alerts
|

Passive removal of immiscible spacers from segmented flows in a microfluidic probe

Abstract: Microfluidic probes (MFPs) are a class of non-contact, scanning microfluidic devices that hydrodynamically confine nanoliter volumes of a processing liquid on a surface immersed in another liquid. So far only chemical processes using a single processing liquid have been implemented using MFPs. In this letter, we present the design and implementation of a probe head that allows segmented two-phase flows to be used, which will enable different chemical species to be sequentially delivered to a surface in defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…Finally, the observed breakthrough pressure of 250 kPa enables this approach to be used where related work [ 10 ] would not. If the membrane port were placed at the end of a microfabricated needle, oil could be driven through the microchannel, carrying droplets at significant speeds and pressures without exceeding the breakthrough pressure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the observed breakthrough pressure of 250 kPa enables this approach to be used where related work [ 10 ] would not. If the membrane port were placed at the end of a microfabricated needle, oil could be driven through the microchannel, carrying droplets at significant speeds and pressures without exceeding the breakthrough pressure.…”
Section: Discussionmentioning
confidence: 99%
“…It is also not capable of sequenced delivery of different chemicals. Very recently, Kaigala et al [ 10 ] showed an improved version of the vertical probe that is capable of delivering isolated chemical sequences using immiscible fluid segmentation, what could be referred to as droplets. Their device is also based on restricting fluid flow to parts of the chip by Laplace or capillary pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The scanning capability of the probe 36 allows the patterning on large surfaces, typically in the centimeter range, with the possibility of creating arrays of up to 30 000 spots/cm 2 with a spot size of 10 × 10 μm 2 . Third, the capacity of the MFP to rapidly switch liquids 37 on top of the substrate makes it a relevant tool for implementing complex biochemistries requiring multiple consecutive chemicals to be dispensed on the surface or even for manufacturing protein microarrays.…”
Section: Discussionmentioning
confidence: 99%
“…This could be done by the controlled insertion and removal of immiscible spacers, thereby minimizing Taylor dispersion. 29 Moreover, we believe it is conceivable to integrate the methods presented with techniques to perform local temperature alterations 30 to assist in performing efficient chemical reactions.…”
Section: Discussionmentioning
confidence: 99%